Factors Influencing the Success of Students’ Learning through Online Learning/Distance Education : A Bibliometric Analysis of Scopus Database - Agus Santoso; Heri Retnawati; Munaya Nikma Rosyada; Ezi Apino; Ibnu Rafi; Kartianom Kartianom; Aigul Dauletkulova (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to examine the co-occurrence of several topics linked to factors that influence student learning success and explore the motor themes related to factors that influence student learning success. This study used the literature review method with data analysis using R Studio and VOSViewer software. Data analyzed were exported from the Scopus website from 2013 to 2023 of 383 documents. The research data analysis techniques used network mapping analysis of VOSviewer results (network visualization) and content analysis within the keywords and studies. The findings of this study presented the keywords (most frequent words, trending topics), co-occurrence network (thematic map and thematic evolution), and discussion of topics related to factors that influence student learning success. The basic themes identified were higher education and Covid-19. Meanwhile, gender and self-efficacy are motor themes that could be researched further as those can influence student learning performance in online learning. The findings of the bibliometric analysis were intended to reveal unique insights into the factors that determine student learning performance in distant learning and contribute to previously unexplored issues.